2002
DOI: 10.1163/15685370260441008
|View full text |Cite
|
Sign up to set email alerts
|

Intuitive Conceptions of Dead Agents' Minds: The Natural Foundations of Afterlife Beliefs as Phenomenological Boundary

Abstract: Little is known about how the minds of dead agents are represented. In the current experiment, individuals with different types of explicit afterlife beliefs were asked in an implicit interview task whether various mental state types, as well as pure biological imperatives, continue after death. The results suggest that, regardless of one's explicit reports about personal consciousness after death, those who believe in some form of life after death (and, to a certain extent, even those who do not) implicitly r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
173
3
5

Year Published

2006
2006
2016
2016

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 208 publications
(189 citation statements)
references
References 39 publications
8
173
3
5
Order By: Relevance
“…Nevertheless, there is evidence that simulation constraints (i.e., the inability to know what it is "like" to be dead) may comprise an important set of factors. Like reasoning about one's past mental states during dreamless sleep or while in other somnambulistic states, consciously representing a final state of unconsciousness poses formidable, if not impassable, cognitive constraints (Barrett 2004;Bering 2002a;Bering & Bjorklund 2004;Bering et al 2005;Clark 1994; Gilbert 2001;Nichols, in press). By relying on simulation strategies to derive information about the minds of dead agents, one would be compelled to put themselves "into the shoes" of such organisms, which is an impossible feat.…”
Section: -Sigmund Freud Thoughts For the Times On War And Deathmentioning
confidence: 99%
See 4 more Smart Citations
“…Nevertheless, there is evidence that simulation constraints (i.e., the inability to know what it is "like" to be dead) may comprise an important set of factors. Like reasoning about one's past mental states during dreamless sleep or while in other somnambulistic states, consciously representing a final state of unconsciousness poses formidable, if not impassable, cognitive constraints (Barrett 2004;Bering 2002a;Bering & Bjorklund 2004;Bering et al 2005;Clark 1994; Gilbert 2001;Nichols, in press). By relying on simulation strategies to derive information about the minds of dead agents, one would be compelled to put themselves "into the shoes" of such organisms, which is an impossible feat.…”
Section: -Sigmund Freud Thoughts For the Times On War And Deathmentioning
confidence: 99%
“…Attempts to simulate dead agents' minds may even result in Type I errors made by adults who profess not to believe in the afterlife. Bering (2002a) found that when undergraduate students were asked to reason about the psychological abilities of a protagonist who had just abruptly died in an automobile accident, even some participants who later classified themselves as "extinctivists" (i.e., those who endorsed the statement "what we think of as the 'soul,' or conscious personality of a person, ceases permanently when the body dies"; after Thalbourne 1996), nevertheless stated that the dead person knew that he was dead.…”
Section: -Sigmund Freud Thoughts For the Times On War And Deathmentioning
confidence: 99%
See 3 more Smart Citations